Special Education in the Arab Gulf Countries: An Analysis of Ideals and Realities - Maha Al-Hendawi (17337730) (2023)
This research examines the status of special education in the Arab Gulf nations of Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, United Arab Emirates in the early 2020s using three methods. First, through an integrative examination of laws, policies, and international commitments to disability rights in the area of education, we describe what these countries are trying to achieve in terms of the education of their children and youth with disabilities—their ideals. We then describe the extent to which those ideals are being achieved—the realities— by (a) classifying the countries’ educational provision for their exceptional learners according to an empirical typology that describes national differences in serving such students educationally and (b) investigating recent literature on special education teacher preparation and special education research in the Arab Gulf states to understand why there may be discrepancies between the ideals and the realities. The countries’ commitment to the right to education for individuals with disabilities is solidly and firmly in place. The reality of fully achieving that ideal is still developing, though progress is being made. Other Information Published in: International Journal of Educational Research Open License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijedro.2022.100217